STUDY ON PREPARATION OF COMPOSITE MATERIAL BASED ONHDPE-LLDPE AND FLY ASH IN MELT STATE - Hoàng, Thái; Giang, Nguyễn Vũ; Thâm, Đỗ Quang; Chinh, Nguyễn Thuý (Vietnam Journal of Science and Technology, 2012)
SUMMARY The composites of high-density polyethylene/linear low-density polyethylene (HDPE/LLDPE (75/25 wt/wt) filled by fly ash (FA) with different contents of FA were prepared by melt mixing in a Haake Rheomixer. The relative melt viscosity of the composites increased with increasing the FA content in PE. The mechanical properties of the composites are lower than those of neat PE and decreased with increasingFA content. After modifying FA with organic silane, the relative melt viscosity of the PE/modified FA (MFA) composites is lower than the PE/original FA (OFA) composites. The tensile strength and the elongation at break of the PE/MFA composites are higher than those of the PE/OFA composites. The comparison of the properties of the composites filled with MFA and OFA revealed that the composites with MFA showed better reinforcing properties. The MFA disperses in PE matrix more regular than the OFA.